Synthesis of Orthogonally N-Protected, C-4 Functionalized Cyclic Guanidines from l-Serine - Silva, Diego R. C.; Maria, Edmilson J.; Suárez Ordóñez, Rosa M.; Thierry, Josiane; Cariou, Kevin; Dodd, Robert H. (Synlett, 2017)
A straightforward and efficient preparation of five-membered cyclic guanidines bearing an ester, a hydroxymethyl or a Weinreb amide functional group at C-4 is described from l-serine. The novel synthetic route provides cyclic guanidines in which the three nitrogen atoms are orthogonally protected making them highly suitable for further transformations into natural products or their analogues via the introduced functional groups.
Keywords: cyclic guanidine; amino acid; azide; orthogonal protection; Weinreb amide